The purchasing habits of consumers concerning online shopping: An empirical study on Dhaka city residents (International Journal of Scientific Research and Management (IJSRM), 2024)
Online shopping has gained immense popularity and importance all over the world. Online shopping across the globe has gained tremendous importance and popularity. When you think about all the ways a chatbot can be used to market to your customers and improve your customer service, it is no wonder why it is positioned as a leading tool for marketing. The research takes a look at consumer behavior in internet shopping on top of this to recognize elements influencing consumers to shop online. It is an empirical research design study. This study was done in Dhaka City, Bangladesh, for a whole month from May 1, 2024, to May 31, 2024. A sampling technique called Convenience Sampling is used to collect 212 samples through Google Forms. The study used both primary and secondary data. The data is shown using bar diagrams, pie charts, and percentages. It was found that people shop online rather than offline. They shop once a month, mainly for electronic gadgets and clothes. And the customer feels super comfy and safe buying stuff online. It was also found that online shopping is cheaper, and the quality of products is good. The research concludes that customer behavior towards online shopping is influenced by various factors like age, gender, price satisfaction level & more. Basically, people’s habits and different things affect how they shop online.